MANAJEMEN PENGETAHUAN MELALUI PERUMUSAN STANDAR OPERASIONAL PROSEDUR BAGIAN HUMAN RESOURCE DEPARTEMENT PADA KANTOR PT XLA CIPTA PERKASA - Zahirah, Andi Anisa; Maulida, St. Nurhikma (ADMIT: Jurnal Administrasi Terapan, 2025)
PT XLA Cipta Perkasa office have SITAC Division, Finance Division, Procurement Division, and Human Resource Division. All divisions do not have and have not implemented Standard Operating Procedure (SOP). Therefore, the purpose of this research is to develop a Standard Operating Procedure for the Human Resource Department (HRD) at PT XLA Cipta Perkasa. The research method used is a qualitative method approach. The results showed that the SOP has a relationship with knowledge management in a company. There are 4 (four) stages used by researchers in preparing SOP, including SOP Need Assessment, SOP Development, SOP Implementation, SOP Monitoring and Evaluation. The conclusion is when compiling a Standard Operating Procedure (SOP), several aspects need to be considered such as the purpose of the document, the quality of the procedure implementation, the format, and the structure of the SOP writing. The researcher's suggestion is that the SOP should be made clearer for the company so that everything can be implemented in accordance with the previously established rules.